The function g(x) = 2x^2 - 1

g(x - h) = 2*(x - h)^2 - 1

=> 2*(x^2 + h^2 - 2xh) - 1

=> 2x^2 + 2h^2 - 4xh - 1

**The expression representing g(x - h) = 2x^2 + 2h^2 - 4xh - 1**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now